Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

solve for g -a=gs   g=

Sagot :

[tex]g -a=gs\\\\g-gs=a\\\\g(1-s)=a\ /:(1-s)\ \ \ and\ \ \ s \neq 1\\\\g= \frac{a}{1-s} [/tex]
AL2006
I think the equation is:

-a = g s

Divide each side by 's':

-a/s = g